Respuesta a precios del área sembrada de soja en la Argentina - Luis Lanteri (Banco Central de la República Argentina (BCRA), Investigaciones Económicas (ie), 2009)
– This paper analyzes the response of the soybean sown area of Argentina to changes in price incentives and other variables which are relevant for agricultural production. To this effect, VEC models are estimated for some of the main producing provinces and for the country's total in the period 1974-2006. The estimated models allow analyzing the long-term relationship among the share of soybean sown area, relative prices, the use of certain inputs, and the risks involved. For models where cointegration relations are observed, positive and significative responses are found in the soybean sown area to changes in relative prices.
Keywords: C1; Q1; R3; 330; agricultural production; Argentina; elasticities; relative prices; risks; soybean